Doing interprofessional research in the COVID-19 era: a discussion paper. Issue 5 (2nd September 2020) - Sy, Michael; O'Leary, Noreen; Nagraj, Shobhana; El-Awaisi, Alla; O'Carroll, Veronica; Xyrichis, Andreas
ABSTRACT: The COVID-19 pandemic, and ensuing physical distancing measures, poses challenges for researchers in the field of interprofessional care. Pandemic management has highlighted the centrality of interprofessional working to effective healthcare delivery during crises. It is essential to find ways to maintain interprofessional research that has commenced, while also designing research to capture important learning from pandemic management and response. However, it also creates opportunities for new research projects and novel research designs. This discussion paper explores ways of adapting existing research methodologies and outlines potential avenues for new research. Specifically, considerations to bear in mind when designing interprofessional research during the pandemic include research ethics and integrity, research design, data collection methods, research opportunities, implications and limitations. Interprofessional research can continue to make a valuable contribution in informing global responses to COVID-19 and in planning for future global health crises. We call for, insofar as possible, for interprofessional research to continue to be developed during this time.